The invasive land flatworm Obama nungara (Platyhelminthes: Geoplanidae) reaches a natural environment in the oceanic island of São Miguel (Açores) - Lago-Barcia, Domingo; González-López, José Rafael; Fernández-Álvarez, Fernando Ángel (Zootaxa, 2020)
During an entomological sampling trip in the island of São Miguel (Açores, Portugal) on 02-11-2019 by José Rafael González-López, one specimen of the invasive flatworm Obama nungara Carbayo et al. 2016 was found under a rock (Fig. 1A). The specimen was photographed in situ and identified by its external morphology based on its large and broad leaf-like body with nearly parallel body margins, narrow and rounded anterior end, rounded posterior end, and dorsal pigmentation consisting of a light brown ground color covered with dark longitudinal and irregular stripes, and ventral surface grayish-white. Recent studies (Justine et al. 2020; Negrete et al. 2020) showed the reliability of photograph-based identification of O. nungara specimens. It is the sixth island where this species has been found (after Guernsey, Great Britain, Ireland, Corsica, and Madeira).